Improving cardiovascular health at population level: 39 community cluster randomised trial of Cardiovascular Health Awareness Program (CHAP). (7th February 2011) - Kaczorowski, Janusz; Chambers, Larry W; Dolovich, Lisa; Paterson, J Michael; Karwalajtys, Tina; Gierman, Tracy; Farrell, Barbara; McDonough, Beatrice; Thabane, Lehana; Tu, Karen; Zagorski, Brandon; Goeree, Ron; et al.
Abstract : Objective To evaluate the effectiveness of the community based Cardiovascular Health Awareness Program (CHAP) on morbidity from cardiovascular disease. Design Community cluster randomised trial. Setting 39 mid-sized communities in Ontario, Canada, stratified by location and population size. Participants Community dwelling residents aged 65 years or over, family physicians, pharmacists, volunteers, community nurses, and local lead organisations. Intervention Communities were randomised to receive CHAP (n=20) or no intervention (n=19). In CHAP communities, residents aged 65 or over were invited to attend volunteer run cardiovascular risk assessment and education sessions held in community based pharmacies over a 10 week period; automated blood pressure readings and self reported risk factor data were collected and shared with participants and their family physicians and pharmacists. Main outcome measure Composite of hospital admissions for acute myocardial infarction, stroke, and congestive heart failure among all community residents aged 65 and over in the year before compared with the year after implementation of CHAP. Results All 20 intervention communities successfully implemented CHAP. A total of 1265 three hour long sessions were held in 129/145 (89%) pharmacies during the 10 week programme. 15 889 unique participants had a total of 27 358 cardiovascular assessments with the assistance of 577 peer volunteers. After adjustment for hospital admission rates in the year before the intervention, CHAP was associated with a 9% relative reduction in the composite end point (rate ratio 0.91, 95% confidence interval 0.86 to 0.97; P=0.002) or 3.02 fewer annual hospital admissions for cardiovascular disease per 1000 people aged 65 and over. Statistically significant reductions favouring the intervention communities were seen in hospital admissions for acute myocardial infarction (rate ratio 0.87, 0.79 to 0.97; P=0.008) and congestive heart failure (0.90, 0.81 to 0.99; P=0.029) but not for stroke (0.99, 0.88 to 1.12; P=0.89). Conclusions A collaborative, multi-pronged, community based health promotion and prevention programme targeted at older adults can reduce cardiovascular morbidity at the population level. Trial registration Current controlled trials ISRCTN50550004 .